Role for adjuvant chemotherapy in patients with resected small cell lung cancer - Du, Lingling; Waqar, Saiama N.; Morgensztern, Daniel (Journal of Thoracic Disease; Vol 8, No 8 (August 01, 2016): Journal of Thoracic Disease, 2016)
Lung cancer is the leading cause of cancer-related mortality in the United States (1). Small cell lung cancer (SCLC) accounts for approximately 13% of all patients with lung cancer (2). SCLC has traditionally been staged using the Veterans’ Affairs Lung Study Group staging system, which subdivides tumors into limited-stage (LS-SCLC) and extensive-stage (ES-SCLC) based on the presence of tumor confinement into one hemithorax and included in one radiotherapy port (3).